Civil society organisations in climate change adaptation: Paani committee’s movement for tidal river management in South-West Bangladesh - Haque, Kazi Nurmohammad Hossainul; Chowdhury, Faiz Ahmed; Chakma, Rigan (BRAC University, 2018)
Background paper for The State of Governance in Bangladesh 2013.